2015
DOI: 10.1063/1.4931998
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresponse force microscopy study on ferroelectric polarization of ferroelectric polymer thin films with various structural configurations

Abstract: Ferroelectric polymer-based memory devices have attracted much attention due to their potential in low-cost flexible memories. However, bad retention property of recorded logic states limited their applications. Though mechanisms of retention degradation in ferroelectric memories are complicated and still an open question, depolarization in ferroelectric polymer layer was regarded as the main influencing factor. Here we reported our piezoresponse force microscopy (PFM) study of retention property of polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In order to use more simple preparation methods, several works have been published aiming to achieve spin-coated ultrathin PVDFbased films with good ferroelectric properties on several functional substrates. 12,13 Besides the ferroelectric functionality of the thin films of P(VDF-TrFE), to obtain full profit from the synergetic properties of the pair ferroelectric/semiconducting polymers, the semiconducting polymer layer should also preserve its functionality, that is, its transport properties. In this context, studying fundamental properties of bilayers of semiconducting/ferroelectric polymers with nanometric dimensions may contribute to better control and device performance in more complicated designs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to use more simple preparation methods, several works have been published aiming to achieve spin-coated ultrathin PVDFbased films with good ferroelectric properties on several functional substrates. 12,13 Besides the ferroelectric functionality of the thin films of P(VDF-TrFE), to obtain full profit from the synergetic properties of the pair ferroelectric/semiconducting polymers, the semiconducting polymer layer should also preserve its functionality, that is, its transport properties. In this context, studying fundamental properties of bilayers of semiconducting/ferroelectric polymers with nanometric dimensions may contribute to better control and device performance in more complicated designs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The seminal work by Bune et al demonstrated that, in the limit of 2D ferroelectric polymer films, ferroelectricity is preserved in 1 nm thick films prepared by the Langmuir Blodgett method (two monolayers). In order to use more simple preparation methods, several works have been published aiming to achieve spin-coated ultrathin PVDF-based films with good ferroelectric properties on several functional substrates. , Besides the ferroelectric functionality of the thin films of P­(VDF-TrFE), to obtain full profit from the synergetic properties of the pair ferroelectric/semiconducting polymers, the semiconducting polymer layer should also preserve its functionality, that is, its transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…33 Furthermore, there are a lot of studies on memory retention in organic ferroelectrics, particularly in P(VDF-TrFE); relatively little of this study has been done in PVDF thin films. 34,35 To the best of our knowledge, such ultralong retention of 20 days in organic ferroelectric has not been reported so far. Although there has been a lot of research done on the retention issue in the inorganic ferroelectric system, such as Pb(Zr,Ti)O 3 , SrBi 2 Ta 2 O 9 , LiNbO 3 , and BiFeO 3 (BFO).…”
Section: ■ Introductionmentioning
confidence: 87%
“…Experimental approaches have investigated the distribution of polarization in the ferroelectric layer and displacement transients in the gate current [22][23][24][25][26][27] These methods expose the overall states of polarization distribution or get information at the surface. However, they do not make a detailed analysis of the electric field around the electrodes.…”
Section: Introductionmentioning
confidence: 99%